Evaluation of the SAMHSA Primary and Behavioral Health Care Integration (PBHCI) Grant Program Final Report (Task 13) - Scharf, Deborah M. (RAND Corporation, 2014)
Primary and Behavioral Health Care Integration (PBHCI) is intended to improve the overall wellness of people with serious mental illness by providing integrated health care services in a setting where the population already receives care. This report describes the results of RAND's evaluation of the PBHCI grants program, including how grantee programs were implemented, whether the program leads to improvements in outcomes, and which program models and features lead to better processes of care and consumer outcomes.